Farmer Perception Of Organic Rice Farming In Subur Farmers Groups, Lubuk Bayas Village, Perbaungan District, Serdang Bedagai Regency - Gustina Siregar; Fuad Saleh Madhi; Desi Novita (Proceeding International Seminar of Islamic Studies, 2019)
The study was conducted using a case study method. Aimed at finding out, income, production level, Break Event Point (BEP) and farmers' perceptions of organic rice farming in the Subur Farmers Group, Lubuk Bayas Village, Perbaungan District, Serdang Bedagai Regency. The sampling technique is saturated sampling (census), if all members of the population are used as samples. As many as 30 respondents in the Subur Farmers Group have implemented organic rice farming. Data collection methods are primary data obtained directly from farmers and secondary data obtained from relevant agencies such as the Central Statistics Agency, Subur Farmers Group Documents and the Head Office of Lubuk Bayas Village. The analytical method used is descriptive and qualitative which is quantitative. This research was conducted in March 2019 in Lubuk Bayas Village, Perbaungan District, Serdang Bedagai Regency. The first problem research results are known that the average farmer's income is Rp. 15,905,000, the total production cost incurred in the amount of Rp. 6,973,357 and the income earned is Rp. 8,931,643. For BEP Production results obtained an average of 678 kg, BEP Price of Rp. 2,670 while the BEP Receipt was Rp. 3,808,610. The second research result is known that farmers have a very effective perception on the benchmark Price (82.26%), Environmentally Friendly (84.8%) and Production Costs (80.11%). While Marketing (74.13%), Mutu and Quality (68.53%) included in the effective category.